39OPooled analysis of efficacy and safety in Asian patients (pts) in the MONALEESA-2, MONALEESA-3, and MONALEESA-7 trials of ribociclib (RIB) plus endocrine therapy (ET). (24th November 2019) - Im, S-A; Yap, Y-S; Sohn, J; Lee, K S; Jung, K H; Tseng, L M; Lee, S C; Babu, K G; Park, Y H; Gounaris, I; Sondhi, M; Ridolfi, A; et al.
Abstract: Background: We performed a pooled analysis of Asian pts in the phase III MONALEESA (ML) trials, which tested ET ± RIB in pts with hormone receptor–positive/human epidermal growth factor receptor-2–negative advanced breast cancer. Methods: ML-2 and ML-3 enrolled postmenopausal pts; ML-7 enrolled pre/perimenopausal pts. To pool a homogenous population and reflect health authority recommended treatment, this analysis included all pts from ML-2, first-line pts from ML-3 and pts treated with a nonsteroidal aromatase inhibitor from ML-7. Results: Pts were assigned to ET + PBO (118 Asian; 562 non-Asian) or ET + RIB (136 Asian; 651 non-Asian). In Asian pts, median PFS was 12.7 mo (95% CI, 9.1-15.6) with PBO vs not reached (NR; 95% CI, 16.6-NR) with RIB (hazard ratio [HR], 0.49 [95% CI, 0.34-0.70]). In non-Asian pts, median PFS was 16.5 mo (95% CI, 14.5-18.2) with PBO vs 25.3 mo (95% CI, 23.8-27.7) with RIB (HR, 0.59 [95% CI, 0.50-0.69]). In 182 Asian pts with visceral mets, median PFS was 12.7 mo (95% CI, 8.8-16.0) with PBO vs 23.9 mo (95% CI, 14.8-NR) with RIB (HR, 0.54 [95% CI, 0.36-0.82]). In 687 non-Asian pts with visceral mets, median PFS was 13.0 mo (95% CI, 11.1-14.9) with PBO vs 23.9 mo (95% CI, 19.9-29.6) with RIB (HR, 0.55; 95% CI, 0.44-0.68). In Asian pts, overall response rate (ORR) was 33.1% (95% CI, 24.6-41.5) with PBO vs 49.3% (95% CI, 40.9-57.7) with RIB (P = 0.005). In non-Asian pts, ORR was 27.8% (95% CI, 24.1-31.5) with PBO vs 38.2% (95% CI, 34.5-42.0) with RIB (P < 0.001). Among pts with visceral mets, ORR was 37.6% (95% CI 27.3-47.9) with PBO vs 52.6% (95% CI, 42.6-62.5) with RIB (P = 0.022) in Asian and 34.5% (95% CI, 29.3-39.7) with PBO vs 44.3% (95% CI, 39.2-49.4) with RIB (P = 0.004) in non-Asian pts. The most common grade 3/4 adverse event (AE) was neutropenia (preferred term) in Asian (47.1%) and non-Asian (45.6%) RIB-treated pts. In the Asian subgroup, 1 pt receiving PBO (0.8%) and 3 pts receiving RIB (2.2%) discontinued due to AEs; in non-Asian pts, 16 receiving PBO (2.8%) and 46 receiving RIB (7.1%) discontinued due to AEs. Conclusions: Significant improvements in PFS and ORR were observed in Asian pts with RIB vs PBO. Discontinuation rates due to AEs were lower in Asian pts. Clinical trial identification: NCT01958021; NCT02422615; NCT02278120. Legal entity responsible for the study: Novartis Pharmaceutical Corporation. Funding: Novartis Pharmaceutical Corporation. Disclosure: S-A. Im: Research grant / Funding (self): AstraZeneca; Advisory / Consultancy: Novartis; Advisory / Consultancy: Hanmi; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Eisai. Y-S. Yap: Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Novartis; Advisory / Consultancy: Pfizer; Travel / Accommodation / Expenses: Eisai; Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy: Roche. K.S. Lee: Advisory / Consultancy: Lily; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Roche; Research grant / Funding (self): Dong-A Socio. L.M. Tseng: Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: Novartis; Honoraria (self), Research grant / Funding (self), Travel / Accommodation / Expenses: Roche Pharma AG; Research grant / Funding (self): MSD; Travel / Accommodation / Expenses: GlaxoSmithKline. S.C. Lee: Honoraria (self): ACT Genomics; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Eisai; Honoraria (self), Advisory / Consultancy: Lilly; Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Pfizer; Research grant / Funding (self): Taiho Pharmaceutical; Travel / Accommodation / Expenses: Amgen. Y.H. Park: Honoraria (self), Travel / Accommodation / Expenses: Merck; Honoraria (self), Travel / Accommodation / Expenses: Novartis; Honoraria (self), Advisory / Consultancy: Pfizer; Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Eisai. I. Gounaris: Non-remunerated activity/ies: PharmaMar; Shareholder / Stockholder / Stock options, Full / Part-time employment: Novartis. M. Sondhi: Shareholder / Stockholder / Stock options, Full / Part-time employment: Novartis. A. Ridolfi: Shareholder / Stockholder / Stock options, Full / Part-time employment: Novartis. J.P. Zarate: Shareholder / Stockholder / Stock options, Full / Part-time employment: Novartis. Y-S. Lu: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (self), Clinical trial study fee; Grant for clinical study for ESR1 mutation detected by cell free DNA;: Novartis; Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): Pfizer; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Research grant / Funding (self): Roche; Research grant / Funding (self): Merck Sharp & Dohme; Research grant / Funding (self): GlaxoSmithKline. All other authors have declared no conflicts of interest.